Islamic-Based Mathematics Learning Model for Islamic Boarding School Students - Maulidiyah, Faizzatul; Aniqotizzahro, Salma; Abadiyah, Sa’diyatul; Fathani, Abdul Halim (SAINTIS Publishing, 2024)
Islamic boarding schools are one of the Indonesian instructive educate that utilize formal and informal curricula. In their learning activities, some students have difficulty taking formal subjects, especially a subject in this research, namely mathematics. This research aimed to develop an Islamic-based mathematics learning model for Islamic boarding school students to suit the students’ needs. The research design was Research Development. Information collection was carried out through interviews, questionnaires, tests, and perception sheets. The research results from the try- out of an Islamic boarding school student mathematics learning model that integrated mathematics with Qur’an values had a significant effect on learning outcomes and increased student motivation in learning. Therefore, this learning model was very feasible and suitable to be implemented for Islamic boarding school students.